Copper Contamination Effects on Phytoplankton-Zooplankton System within Deterministic and Stochastic Environments (Journal of Nonlinear Modeling and Analysis, 2024)
Since the aquatic organisms are very sensitive to the increasingcopper contamination in water, this paper focuses on investigating the effectsof copper contamination on the interaction between phytoplankton and zooplankton species within both deterministic and stochastic environments. Wefirst construct a deterministic phytoplankton-zooplankton interaction modelcoupled with the copper concentration and analyze its dynamics, includingexistence and stability of equilibria, as well as the existence of Hopf bifurcation. A new stochastic model is derived in the form of continuous-time Markovchain (CTMC), and branching process theory is applied to the CTMC modelto estimate the extinction probability of zooplankton species. Analytical andnumerical findings show that the destiny of species is closely related to thecopper concentration, and the predictions of the deterministic and stochasticmodels may be different in some cases.
Keywords: Phytoplankton-zooplankton system; copper contamination; CTMC model; extinction probability.